Epizootiological Survey of the Isle Russian and Measures Necessary for the Prophylaxis of Tick-Born Infections among Population of the Region and Participants of APEC Summit - S. V. Balakhonov; A. Ya. Nikitin; T. V. Zvereva; R. V. Adel'shin; A. V. Allenov; E. I. Andaev; E. A. Borisenko; T. I. Borisova; Yu. A. Verzhutskaya; E. A. Vershinin; N. S. Gordeyko; V. T. Klimov; et al. (Проблемы особо опасных инфекций, 2012)
In spring, 2011 within the frames of epizootiological survey of the Isle Russian territory, identified were five species of Ixodic ticks: Ixodes persulcatus, I. pavlovskyi, Haemaphysalis concinna, H. japonica douglasi, Dermacentor silvarum. Those ticks were infected with the agents of tick-born encephalitis, borreliosis, rickettsiosis, and monocytic ehrlichiosis. Further preparations for the hosting of APEC Summit in the territory of the Isle in September 2012 involve large-scale construction of various facilities, transformation of natural biotopes, and significant increase in population numbers both permanently and temporally residing in the region. In this connection, a complex of preventive measures aimed at protection of local population and participants of the Summit from tick-borne infections is currently under consideration.